Geração Procedimental de Mundos 3D Infinitos para Jogos - Luís Miguel Coelho e Magalhães (2017)
Procedural Generation is commonly used to develop mass content, in a parametrized way. It hasbeen used over the last few years for the creation of, for example, 3D objects, and realistic orartificial natural environments.Although some recent digital games, such as Minecraft or No Man's Sky present infinite worldsgeneration, these lack complex structures, such as roads, rivers or cities. Furthermore, scientificstudies on the area of procedural [world] generation are not yet focused on infinite generation,particularly the study of infinite game worlds.Given that infinite worlds cannot be generated as a whole - since memory and expected generationtimes are limited -, those must be generated in a fractioned manner. As such, the mainissue when generating these worlds is to maintain continuity and consistency of continuous elementsthat cross the borders of generated content, such as roads or cities. With this in mind, oncethis problem is overcome, the generation of infinite worlds might be applied to open worlds fordigital games, virtual simulators (for example, combat of flight simulators), virtual tourism, urbanplanning, publicity or even decorative art.This work presents a deterministic approach to procedurally generate an infinite and complexgame world, battling the continuity issue that arises with infinite worlds and bridging the gapbetween the vast knowledge applied to finite environments and infinite procedural generation. Itwill survey the existing methods to procedurally generate game worlds and composing elements,followed by the methodologies and proposed approaches to solve continuity problems, along withthe work plan and the tools to be used.